Pengaruh Kualitas Layanan, Citra, Fasilitas dan Harga terhadap Kepuasan Pasien pada Rumah Sakit Swasta Tipe B Daerah Surabaya Timur - Limanto, Sherly; Yuliana, Yuliana; Bernarto, Innocentius (J-MAS (Jurnal Manajemen dan Sains), 2024)
The aim of this research is to examine and analyze the influence of service quality, hospital’s image, facilities and prices on patient satisfaction. The research method used survey method with cross-section data collection through questionnaires. The sample was obtained by convenience sampling as many as 78 peoples who received treatment at the type B private hospitals in the East Surabaya City area. The data analysis method used in hypothesis testing is Structural Equation Modeling (SEM). The research results provide evidence that service quality and prices have a positive effect on patient satisfaction. While the image of Hospital and facilities have no effect on patient satisfication.